Asian American adolescents' mental health literacy and beliefs about helpful strategies to address mental health challenges at school. Issue 10 (26th January 2022) - Liu, Jia Li; Wang, Cixin; Do, Kieu Anh; Bali, Diksha
Abstract: Asian Americans are the fastest‐growing racial group in the United States. Contrary to the model minority myth, many Asian American youth experience mental health challenges. However, they are less likely to utilize school‐based mental health services than their non‐Asian American peers. A paucity of research addresses Asian American adolescents' understanding of mental health disorders and beliefs about helpful strategies for addressing psychological challenges within the school context. The present study utilized vignettes and semi‐structured interviews with 24 Asian American adolescents ( M = 16.92, SD = 2.45, 79.17% females) to explore their understanding of eating disorders and depression and what they perceive as helpful strategies to address mental health challenges at school. Participants shared culture‐specific risk factors for these mental health disorders, such as high academic pressure, sociocultural pressures for thinness, and internalized model minority stereotype. Participants also proposed strategies to support youth mental health, including providing support, encouraging professional help‐seeking, reducing stigma, addressing confidentiality concerns, implementing school‐wide programs to promote mental health awareness, promoting positive coping strategies, and establishing strong connections between mental health providers and Asian American students. We discuss practical implications for school‐based mental health programs, practices, and providers. Keypoints: Asian American adolescents shared culture‐specific risk factors for mental health disorders, and proposed strategies to support Asian American youth's mental health (e.g., reducing stigma, addressing confidentiality concerns, implementing school‐wide mental health programs). School mental health professionals should acknowledge potential biases and stereotypes toward Asian American students, address cultural‐specific risk factors (e.g., model minority stereotypes), involve parents, and promote mental health literacy among both parents and youth to support Asian American students' mental health.